ORGANIZING DEBATES FOR DEVELOPING CRITICAL THINKING AND SPEAKING SKILLS OF STUDENTS IN TEACHING A FOREIGN LANGUAGE (Scientific journal of the Fergana State University, 2023)
The article discusses one of the methods of critical thinking, conducting the debate of Karl Popper in teaching foreign languages, including English. The methodology of conducting debates is also described, and also the author pointed out the importance of utilizing the following pedagogical methodology during English teaching classes.